On-the-job training and the effects of insider power - Díaz-Vázquez, P; Snower, D (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2003)
Suppose insiders use their market power to push up their wages, while entrants receive their reservation wages. How will employment be affected? In addressing this question, we focus on the role of on-the-job training. We show that an insider wage hike reduces recession-time employment but, in the presence of on-the-job training can make insider wage hikes less detrimental to average employment (over booms and recessions). We show that when such training is sufficiently high and when economic shocks are sufficiently transient, an insider wage hike may even lead to a rise in average employment.